Health-Related Quality of Life in Transplant-Ineligible Patients With Newly Diagnosed Multiple Myeloma: Findings From the Phase III MAIA Trial. Issue 3 (20th January 2021) - Perrot, Aurore; Facon, Thierry; Plesner, Torben; Usmani, Saad Z.; Kumar, Shaji; Bahlis, Nizar J.; Hulin, Cyrille; Orlowski, Robert Z.; Nahi, Hareth; Mollee, Peter; Ramasamy, Karthik; Roussel, Murielle; et al.
Abstract : PURPOSE: To evaluate the effects of daratumumab, lenalidomide, and dexamethasone (D-Rd) versus lenalidomide and dexamethasone (Rd) on patient-reported outcomes (PROs) in the phase III MAIA study. PATIENTS AND METHODS: PROs were assessed on the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30-item and the EuroQol 5-dimensional descriptive system at baseline and every 3 months during treatment. By mixed-effects model, changes from baseline are presented as least squares means with 95% CIs. RESULTS: A total of 737 transplant-ineligible (TIE) patients with newly diagnosed multiple myeloma were randomly assigned to D-Rd (n = 368) or Rd (n = 369). Compliance with PRO assessments was high at baseline (> 90%) through month 12 (> 78%) for both groups. European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30-item global health status scores improved from baseline in both groups and were consistently greater with D-Rd at all time points. A global health status benefit was achieved with D-Rd, regardless of age (< 75 and ≥ 75 years), baseline Eastern Cooperative Oncology Group (ECOG) performance status score, or depth of response. D-Rd treatment resulted in significantly greater reduction in pain scores as early as cycle 3 ( P = .0007 v Rd); the magnitude of change was sustained through cycle 12. Reductions in pain with D-Rd were clinically meaningful in patients regardless of age, ECOG status, or depth of response. Similarly, PRO improvements were observed with D-Rd and Rd on the EuroQol 5-dimensional descriptive system visual analog scale score. CONCLUSION: D-Rd compared with Rd was associated with faster and sustained clinically meaningful improvements in PROs, including pain, in transplant-ineligible patients with newly diagnosed multiple myeloma regardless of age, baseline ECOG status, or depth of treatment response.